2021
DOI: 10.1038/s41598-021-87018-z
|View full text |Cite
|
Sign up to set email alerts
|

How peptic ulcer disease could potentially lead to the lifelong, debilitating effects of chronic fatigue syndrome: an insight

Abstract: Chronic Fatigue Syndrome (CFS) has been defined as unexplained relapsing or persistent fatigue for at least 6 consecutive months. Immuno-inflammatory pathway, bacterial infection, and other causes play essential roles in CFS. Helicobacter pylori infection is one of the most common causes of foregut inflammation, leading to peptic ulcer disease (PUD). This study aimed to analyze the risk of CFS development between patients with and without PUD. Other related factors were also analyzed. We performed a retrospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 60 publications
1
6
0
3
Order By: Relevance
“…They suggested a three-step progression where excessive use of antibiotics in childhood might lead to typical abdominal symptoms of IBS and, years later, to the development of chronic inflammatory diseases possibly including ME/CFS ( 192 ). A similar hypothesis was stated by Kuo et al., who showed a significantly increased risk in women of developing ME/CFS following Helicobacter pylori associated peptic ulcer disease in a recent retrospective cohort study ( 193 ).…”
Section: The Role Of the Gut Microbiome In Me/cfssupporting
confidence: 79%
“…They suggested a three-step progression where excessive use of antibiotics in childhood might lead to typical abdominal symptoms of IBS and, years later, to the development of chronic inflammatory diseases possibly including ME/CFS ( 192 ). A similar hypothesis was stated by Kuo et al., who showed a significantly increased risk in women of developing ME/CFS following Helicobacter pylori associated peptic ulcer disease in a recent retrospective cohort study ( 193 ).…”
Section: The Role Of the Gut Microbiome In Me/cfssupporting
confidence: 79%
“…A total of 105 and 79 individuals were included in the patient and control groups, respectively. The female-to-male ratio was 77: 28 1).…”
Section: Resultsmentioning
confidence: 94%
“…Fatigue is a common complaint in other chronic diseases and gastrointestinal diseases besides MS. Thus, H. pylori may need to be investigated as a cause of fatigue, especially in patients with chronic diseases, who were selected in our study (28).…”
Section: Discussionmentioning
confidence: 99%
“…The etiologies of chronic fatigue syndrome involve multiple factors. Current studies revealed the etiologies are related to infection [ 8 ], immune system differences [ 9 ], endocrine-metabolic dysfunction [ 10 ], or some specific disease such as peptic ulcer disease [ 11 ]. Multiple infectious agents have been linked to CFS, such as the varicella zoster virus [ 9 ].…”
Section: Introductionmentioning
confidence: 99%